PENGARUH IKLIM ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP PRODUKTIVITAS - Muslimah Muslimah (Jurnal Manajemen Pendidikan, 2013)
The objective of this research is to study information about the effect of organizational climate and organizational citizenship behavior (OCB) on the productivity. Ministry of National Education of Indonesia by using survey method with path analysis applied in testing hypothesis. The sample size in the research was done to 74 headmaster with samples taken using simple random sampling. The data were analyzed by using descriptive analyses, regressive analysis, and line analysis method. The result shows that there are direct influence of the followings: (1) there is positively direct effect of organizational climate on the productivity, (2) there is positively direct effect of organizational citizenship behavior (OCB) on the productivity (3) there is positively direct effect of organizational climate on the organizational citizenship behavior (OCB). It is expected that the results of the research could be implied in increasing and optimalizing the productivity, organizational climate , and organizational citizenship behavior(OCB) should be taken into account.